A Florida-Friendly Landscaping™ Approach to Pest Management in Your Edible Landscape - Tina McIntyre; Rachel Gutner; Hamutahl Cohen; Tiare Silvasy; Esen Momol (EDIS)
This new 8-page publication of the UF/IFAS Environmental Horticulture Department defines different types of pests that a home gardener might encounter and encourages diversifying landscapes as a solution to pest problems. It focuses on what is called “the triangle” of IPM, a guide to managing pests using multiple methods, and provides examples of Integrated Pest Management tools that can be applied in the home context to address these pests. Several links to resources relevant to edible Florida-Friendly landscapes are included. Written by Tina McIntyre, Rachel Gutner, Hamutahl Cohen, Tiare Silvasy, and Esen Momol. https://edis.ifas.ufl.edu/ep629